A formula and production process of phosphogypsum autoclaved aerated concrete blocks
By using the combination of phosphogypsum and composite foaming agent in the production of autoclaved aerated concrete blocks, the problems of uneven stirring, high cost and radioactive pollution in the prior art are solved, and more efficient and safer production is achieved Process and product performance.
Patent Information
- Application Number
- CN202410935137.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-12
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-07-12
AI Technical Summary
The existing autoclaved aerated concrete blocks have problems such as uneven mixing, high cost, poor frost resistance and radioactive pollution during the production process, which affect product quality and human health.
Using phosphogypsum as a foaming agent, combining sodium dodecyl sulfate, sodium sulfate of octadecyl ethylene ether and sodium phosphate monoester, and reacting carboxymethyl cellulose with epoxy starch The obtained foam stabilizer is prepared by using specific ball milling, stirring and autoclaving maintenance processes to prepare phosphogypsum autoclaved aerated concrete blocks.
It improves the volume stability and compressive strength of aerated concrete, reduces production costs, reduces radioactive pollution, and improves the product's frost resistance and combined performance with mortar.
Smart Images

Figure BDA0004941079890000081 
Figure BDA0004941079890000091
Abstract
Description
Technical Field
[0001] The invention relates to the field of aerated concrete, in particular to a formula and a production process of a phosphogypsum autoclaved aerated concrete block. Background Art
[0002] Aerated concrete blocks are solid blocks made of cement, slag, sand, lime, etc. as the main raw materials, with the addition of gas-generating agents, and are formed by mixing, molding, and autoclaving. Aerated concrete can be divided into five types according to its use: non-load-bearing blocks, load-bearing blocks, insulation blocks, wall panels, and roof panels. Aerated bricks have the advantages of light bulk density, high thermal insulation performance, good sound absorption, certain strength and processability. It is one of the earliest and most widely used lightweight wall materials in my country. The vast majority of aerated concrete products in my country are blocks, most of which are used for filling and maintenance structures of frame structures.
[0003] Autoclaved aerated concrete blocks with fly ash as the main raw material have certain defects, such as: excessive radioactive substances, tight supply and demand of raw materials, poor frost resistance, poor combination with mortar during masonry construction, easy to cause wall falling and other quality accidents, especially radioactive pollution seriously endangers human health. At the same time, the current production method of aerated concrete blocks is to mix various raw materials, then mix and stir with water in proportion, shape, pressurize and maintain. Since this method mixes all raw materials together, it requires high-power mixing equipment, which is costly and easy to mix unevenly, affecting product quality. Summary of the invention
[0004] The object of the present invention is to provide a formula and a production process of phosphogypsum autoclaved aerated concrete blocks to solve the problems raised in the above background technology.
[0005] In order to solve the above technical problems, the present invention provides the following technical solution: a phosphogypsum autoclaved aerated concrete block, which comprises the following raw materials in parts by weight: 50 to 60 parts of slag, 20 to 40 parts of graphite tailings, 9 to 12 parts of quicklime, 4 to 6 parts of alkali components, 2 to 5 parts of foaming agent, 1 to 2 parts of catalyst and 1 to 4 parts of foam stabilizer.
[0006] Preferably, the foaming agent includes sodium lauryl sulfate, sodium salt of octadecyl alcohol polyoxyethylene ether sulfate, sodium salt of phosphate monoester and phosphogypsum.
[0007] Preferably, the foam stabilizer is cellulose starch; the cellulose starch is prepared by reacting carboxymethyl cellulose and epoxy starch.
[0008] Preferably, the alkali component includes water glass and sodium hydroxide.
[0009] Preferably, the catalyst is manganese dioxide.
[0010] Preferably, a production process of phosphogypsum autoclaved aerated concrete blocks comprises the following specific steps:
[0011] (1) ball-milling slag, graphite tailings and quicklime to 190-220 meshes respectively, and mixing them according to the mass ratio to obtain mixed powder;
[0012] (2) mixing sodium lauryl sulfate, sodium salt of octadecyl alcohol polyoxyethylene ether sulfate, sodium salt of phosphate monoester and phosphogypsum in a mass ratio of 5-7:2:2:1-3, and stirring to obtain a foaming agent;
[0013] (3) mixing epoxy starch and anhydrous ethanol in a mass ratio of 1:8-10, stirring evenly, adjusting the pH to 3.8-4.2 with glacial acetic acid, adding carboxymethyl cellulose of the same mass as the epoxy starch, stirring at 400-800 rpm for 24 hours, centrifuging and washing with anhydrous ethanol for 3-5 times, and vacuum drying to obtain a foam stabilizer;
[0014] (4) Mix sodium hydroxide and deionized water, let stand and cool, then add water glass with a modulus of 1.5 to 1.8, stir evenly, let stand for 18 to 24 hours, and prepare an alkali component;
[0015] (5) Mixing the mixed powder, alkali component, foaming agent, catalyst and foam stabilizer, stirring evenly to obtain slurry, injection molding, pre-curing, autoclaving and curing to obtain phosphogypsum autoclaved aerated concrete blocks.
[0016] Preferably, in the above step (2), the preparation method of stearyl alcohol polyoxyethylene ether sodium sulfate is: heating stearyl alcohol polyoxyethylene ether to 48-52° C., adding chlorosulfonic acid in an amount of 1 to 1.2 times the mass of stearyl alcohol polyoxyethylene ether at a rate of 1 to 3 mL / min, reacting for 15 to 25 minutes, heating to 62 to 64° C., adjusting the pH to 8.8 to 9.2 with sodium hydroxide, rotary evaporating and then dissolving with anhydrous ethanol to obtain stearyl alcohol polyoxyethylene ether sodium sulfate.
[0017] Preferably, in the above step (2), the preparation method of the sodium salt of phosphate monoester is: cyclohexane and N,N-dihydroxyethyl dodecylamine are mixed in a mass ratio of 20 to 40:1, and after stirring to dissolve, phosphoric acid in an amount of 4 to 6 times the mass of N,N-dihydroxyethyl dodecylamine is added, the temperature is raised to 85 to 95°C, and the temperature is kept to react for 3 to 4 hours, and then the temperature is further raised to 110 to 120°C, and the reaction is carried out for 6 to 8 hours, and then sodium hydroxide in an amount of 1.6 to 1.8 times the mass of N,N-dihydroxyethyl dodecylamine is added, and the reaction is carried out for 1 to 2 hours to obtain the sodium salt of phosphate monoester.
[0018] Preferably, in the above step (3), the preparation method of epoxy starch is: starch, ethyl acetate, epichlorohydrin and pyridine are mixed in a mass ratio of 1:6-8:10-20:3, the oil bath is heated to 160-180°C, reacted at 400-600rpm for 2-3h, filtered and washed with anhydrous ethanol for 3-5 times, ultrasonicated at 60-80kHz for 30-60s, and finally dried to obtain epoxy starch.
[0019] Preferably, in the above step (5), the pre-curing temperature is 48-50°C and the time is 4-5 hours; the pressure of the autoclave curing is 0.9-1.1 MPa, the temperature is 160-180°C and the time is 5-6 hours.
[0020] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0021] The phosphogypsum autoclaved aerated concrete block of the present invention comprises slag, graphite tailings, alkali components, foaming agent, catalyst and foam stabilizer;
[0022] The composite foaming agent includes sodium dodecyl sulfate, sodium salt of octadecyl alcohol polyoxyethylene ether sulfate, sodium salt of phosphate monoester and phosphogypsum. Sodium dodecyl sulfate, sodium salt of octadecyl alcohol polyoxyethylene ether sulfate and sodium salt of phosphate monoester are compounded for foaming, and non-ionic surfactants of different long chains are added. Since the low polar groups in the molecules have no repulsion of like charges, they are very easy to get close to each other. Therefore, when they are arranged on the surface of the solution, the density of the hydrophobic groups will increase, the surface tension of the solution will decrease, and the surface activity will increase, thereby improving the foaming power. Then phosphogypsum is added. Phosphogypsum contains a large amount of sulfur trioxide, which has a foaming effect after heating, thereby enhancing the foam height and thus enhancing the stability of the foam.
[0023] The foam stabilizer is cellulose starch, which is obtained by the reaction of carboxymethyl cellulose and epoxy starch; carboxymethyl cellulose reacts with epoxy starch to form macromolecules with a cross-linked network structure, which can enhance the active molecules of surface adsorption and the thickener that can increase the viscosity of the foam stock solution. After being compounded with the alkali component, it can accelerate the coagulation and hardening and improve the strength; the slurry prepared by mixing slag, graphite tailings powder, alkali component, foaming agent, catalyst and foam stabilizer is autoclaved and cured to improve the volume stability of aerated concrete. DETAILED DESCRIPTION
[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0025] The slag in the present invention was purchased from Jiangsu Lianxin Concrete Co., Ltd., and the graphite tailings was purchased from Hubei Yichang Chencheng Graphite Co., Ltd.
[0026] Example 1
[0027] The weight proportions of the components in this embodiment are: 50 parts of slag, 20 parts of graphite tailings, 9 parts of quicklime, 4 parts of alkali component, 2 parts of foaming agent, 1 part of catalyst manganese dioxide and 1 part of foam stabilizer;
[0028] The production process of phosphogypsum autoclaved aerated concrete blocks in this embodiment is as follows:
[0029] (1) ball-milling slag, graphite tailings and quicklime to 190 mesh respectively, and mixing them according to the mass ratio to obtain mixed powder;
[0030] (2) The temperature of octadecanol polyoxyethylene ether was raised to 48°C, chlorosulfonic acid (1 times the mass of octadecanol polyoxyethylene ether) was added dropwise at 1 mL / min, the reaction was continued for 15 min, the temperature was raised to 62°C, the pH was adjusted to 8.8 with sodium hydroxide, the mixture was rotary evaporated and then dissolved with anhydrous ethanol to obtain sodium octadecanol polyoxyethylene ether sulfate; cyclohexane and N,N-dihydroxyethyl dodecylamine were mixed at a mass ratio of 20:1, stirred and dissolved, phosphoric acid (4 times the mass of N,N-dihydroxyethyl dodecylamine) was added, the temperature was raised to 85°C, the temperature was kept for reaction for 3 h, the temperature was continued to be raised to 110°C, the reaction was continued for 6 h, and sodium hydroxide (1.6 times the mass of N,N-dihydroxyethyl dodecylamine) was added, and the reaction was continued for 1 h to obtain sodium monophosphate; sodium lauryl sulfate, sodium monophosphate, sodium monophosphate and phosphogypsum were mixed at a mass ratio of 5:2:2:1, and stirred to obtain a foaming agent;
[0031] (3) Starch, ethyl acetate, epichlorohydrin and pyridine were mixed in a mass ratio of 1:6:10:3, heated to 160°C in an oil bath, reacted at 400 rpm for 2 h, filtered and washed with anhydrous ethanol three times, ultrasonicated at 60 kHz for 30 s, and finally dried to obtain epoxy starch; epoxy starch and anhydrous ethanol were mixed in a mass ratio of 1:8, stirred evenly, adjusted the pH to 3.8 with glacial acetic acid, added carboxymethyl cellulose of the same mass as epoxy starch, stirred at 400 rpm for 24 h, centrifuged and washed with anhydrous ethanol three times, and vacuum dried to obtain a foam stabilizer;
[0032] (4) Mix sodium hydroxide and deionized water, let stand and cool, then add water glass with a modulus of 1.5, stir evenly, and let stand for 18 hours to obtain an alkali component;
[0033] (5) Mix the mixed powder, alkali component, foaming agent, catalyst and foam stabilizer, stir evenly to obtain slurry, injection mold, pre-curing, and autoclave curing. The pre-curing temperature is 48° C. and the time is 4 h; the autoclave curing pressure is 0.9 MPa, the temperature is 160° C., and the time is 5 h, to obtain phosphogypsum autoclaved aerated concrete blocks.
[0034] Example 2
[0035] The weight proportions of the components in this embodiment are: 55 parts of slag, 30 parts of graphite tailings, 11 parts of quicklime, 5 parts of alkali component, 3 parts of foaming agent, 1.5 parts of catalyst manganese dioxide and 3 parts of foam stabilizer;
[0036] The production process of phosphogypsum autoclaved aerated concrete blocks in this embodiment is as follows:
[0037] (1) ball-milling slag, graphite tailings and quicklime to 200 meshes respectively, and mixing them according to the mass ratio to obtain mixed powder;
[0038] (2) raising the temperature of octadecanol polyoxyethylene ether to 50°C, adding chlorosulfonic acid in an amount of 1.1 times the mass of octadecanol polyoxyethylene ether at a rate of 2 mL / min, reacting for 20 minutes, raising the temperature to 63°C, adjusting the pH to 9.0 with sodium hydroxide, rotary evaporating, and dissolving with anhydrous ethanol to obtain sodium octadecanol polyoxyethylene ether sulfate; mixing cyclohexane and N,N-dihydroxyethyl dodecylamine at a mass ratio of 30:1, stirring to dissolve, adding phosphoric acid in an amount of 5 times the mass of N,N-dihydroxyethyl dodecylamine, raising the temperature to 90°C, keeping the temperature for reaction for 3.5 hours, and then continuing to raise the temperature to 115°C, reacting for 7 hours, and then adding sodium hydroxide in an amount of 1.7 times the mass of N,N-dihydroxyethyl dodecylamine, and reacting for 1.5 hours to obtain sodium monophosphate; mixing sodium lauryl sulfate, sodium monophosphate, sodium monophosphate, and phosphogypsum at a mass ratio of 6:2:2:2, and stirring to obtain a foaming agent;
[0039] (3) Starch, ethyl acetate, epichlorohydrin and pyridine were mixed in a mass ratio of 1:7:15:3, heated to 170°C in an oil bath, reacted at 500 rpm for 2.5 h, filtered and washed with anhydrous ethanol 4 times, ultrasonicated at 70 kHz for 45 s, and finally dried to obtain epoxy starch; epoxy starch and anhydrous ethanol were mixed in a mass ratio of 1:9, stirred evenly, adjusted the pH to 4.0 with glacial acetic acid, added carboxymethyl cellulose of the same mass as epoxy starch, stirred at 600 rpm for 24 h, centrifuged and washed with anhydrous ethanol 4 times, and vacuum dried to obtain a foam stabilizer;
[0040] (4) Mix sodium hydroxide and deionized water, let stand and cool, then add water glass with a modulus of 1.6, stir evenly, and let stand for 22 hours to obtain an alkali component;
[0041] (5) Mix the mixed powder, alkali component, foaming agent, catalyst and foam stabilizer, stir evenly to obtain slurry, injection mold, pre-curing, and autoclave curing. The pre-curing temperature is 49° C. and the time is 4.5 h; the autoclave curing pressure is 1 MPa, the temperature is 170° C., and the time is 5.5 h, to obtain phosphogypsum autoclaved aerated concrete blocks.
[0042] Example 3
[0043] In this embodiment, the weight proportions of the components are: 60 parts of slag, 40 parts of graphite tailings, 12 parts of quicklime, 6 parts of alkali component, 5 parts of foaming agent, 2 parts of catalyst manganese dioxide and 4 parts of foam stabilizer;
[0044] The production process of phosphogypsum autoclaved aerated concrete blocks in this embodiment is as follows:
[0045] (1) ball-milling slag, graphite tailings and quicklime to 220 meshes respectively, and mixing them according to the mass ratio to obtain mixed powder;
[0046] (2) The temperature of octadecanol polyoxyethylene ether was raised to 52° C., chlorosulfonic acid (1.2 times the mass of octadecanol polyoxyethylene ether) was added dropwise at 3 mL / min, the reaction was continued for 25 min, the temperature was raised to 64° C., the pH was adjusted to 9.2 with sodium hydroxide, the mixture was rotary evaporated and then dissolved with anhydrous ethanol to obtain sodium octadecanol polyoxyethylene ether sulfate; cyclohexane and N,N-dihydroxyethyl dodecylamine were mixed at a mass ratio of 40:1, stirred and dissolved, phosphoric acid (6 times the mass of N,N-dihydroxyethyl dodecylamine) was added, the temperature was raised to 95° C., the reaction was kept warm for 4 h, the temperature was further raised to 120° C., the reaction was continued for 8 h, and sodium hydroxide (1.8 times the mass of N,N-dihydroxyethyl dodecylamine) was added, and the reaction was continued for 2 h to obtain sodium monophosphate; sodium lauryl sulfate, sodium monophosphate, sodium monophosphate and phosphogypsum were mixed at a mass ratio of 7:2:2:3, and stirred to obtain a foaming agent;
[0047] (3) Starch, ethyl acetate, epichlorohydrin and pyridine were mixed in a mass ratio of 1:8:20:3, heated to 180°C in an oil bath, reacted at 600 rpm for 3 h, filtered and washed with anhydrous ethanol for 5 times, ultrasonicated at 80 kHz for 60 s, and finally dried to obtain epoxy starch; epoxy starch and anhydrous ethanol were mixed in a mass ratio of 1:10, stirred evenly, adjusted the pH to 4.2 with glacial acetic acid, added carboxymethyl cellulose of the same mass as epoxy starch, stirred at 800 rpm for 24 h, centrifuged and washed with anhydrous ethanol for 5 times, and vacuum dried to obtain a foam stabilizer;
[0048] (4) Mix sodium hydroxide and deionized water, let stand and cool, then add water glass with a modulus of 1.8, stir evenly, and let stand for 24 hours to obtain an alkali component;
[0049] (5) Mix the mixed powder, alkali component, foaming agent, catalyst and foam stabilizer, stir evenly to obtain slurry, injection mold, pre-curing, and autoclave curing. The pre-curing temperature is 50° C. and the time is 5 h; the autoclave curing pressure is 1.1 MPa, the temperature is 180° C., and the time is 6 h, to obtain phosphogypsum autoclaved aerated concrete blocks.
[0050] Comparative Example 1
[0051] The composition of Comparative Example 1 is the same as that of Example 2. The formula and production process of the phosphogypsum autoclaved aerated concrete block are different from those of Example 2 in that the composite foaming agent only includes sodium dodecyl sulfate, sodium salt of phosphoric acid monoester and phosphogypsum.
[0052] Comparative Example 2
[0053] The composition of Comparative Example 2 is the same as that of Example 2. The formula and production process of the phosphogypsum autoclaved aerated concrete block are different from those of Example 2 in that the composite foaming agent only includes sodium lauryl sulfate, sodium salt of octadecyl alcohol polyoxyethylene ether sulfate and phosphogypsum.
[0054] Comparative Example 3
[0055] The composition of Comparative Example 3 is the same as that of Example 2. The formula and production process of the phosphogypsum autoclaved aerated concrete block are different from those of Example 2 in that the composite foaming agent includes sodium lauryl sulfate, sodium salt of octadecyl alcohol polyoxyethylene ether sulfate and sodium salt of phosphoric acid monoester.
[0056] Comparative Example 4
[0057] The composition of Comparative Example 4 is the same as that of Example 2. The formula and production process of the phosphogypsum autoclaved aerated concrete block are different from those of Example 2 in that the foam stabilizer is only carboxymethyl cellulose.
[0058] Comparative Example 5
[0059] The composition of Comparative Example 5 is the same as that of Example 2. The formula and production process of the phosphogypsum autoclaved aerated concrete block are different from those of Example 2 in that the foam stabilizer includes carboxymethyl cellulose and epoxy starch.
[0060] Effect example
[0061] Table 1 below shows the performance analysis results of the phosphogypsum autoclaved aerated concrete blocks prepared using Examples 1 to 3 of the present invention and Comparative Examples 1 to 5:
[0062] Table 1
[0063]
[0064]
[0065] By comparing the experimental data of the examples and the comparative examples in Table 1, it can be clearly found that the phosphogypsum autoclaved aerated concrete blocks prepared using Examples 1, 2 and 3 have excellent compressive strength and bulk density.
[0066] From the comparison of the experimental data of Example 1, Example 2, Example 3 and Comparative Example 1, Comparative Example 2, Comparative Example 3, it can be found that when sodium lauryl sulfate, sodium salt of octadecyl polyoxyethylene ether sulfate and sodium salt of phosphate monoester are compounded for foaming, and non-ionic surfactants of different long chains are added, since the low polar groups in the molecules have no repulsion of like charges, they are very easy to get close to each other. Therefore, when they are arranged on the surface of the solution, the density of the hydrophobic groups will increase, the surface tension of the solution will decrease, and the surface activity will increase, thereby improving the foaming power. Then, phosphogypsum is added. Phosphogypsum contains a large amount of sulfur trioxide, which has a foaming effect after heating, thereby enhancing the foam height and thus enhancing the stability of the foam.
[0067] From the comparison of the experimental data of Example 1, Example 2, Example 3 and Comparative Example 4, Comparative Example 5, it can be found that carboxymethyl cellulose reacts with epoxy starch to form macromolecules with a cross-linked network structure, active molecules that can enhance surface adsorption and thickeners that can increase the viscosity of the foam stock solution, and after being compounded with the alkali component, coagulation and hardening can be accelerated, and the strength can be improved; slag, graphite tailings powder, alkali component, foaming agent, catalyst and foam stabilizer are mixed to prepare a slurry and then autoclaved and cured to improve the volume stability of aerated concrete.
[0068] Obviously, the above embodiments are merely examples for clearly illustrating the embodiments of the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. However, these obvious changes or modifications derived from the spirit of the present invention are still within the scope of protection of the present invention.
Claims
1. A phosphogypsum autoclaved aerated concrete block, characterized in that: The phosphogypsum autoclaved aerated concrete block comprises the following raw materials in parts by weight: 50-60 parts of slag, 20-40 parts of graphite tailings, 9-12 parts of quicklime, 4-6 parts of alkali components, 2-5 parts of foaming agents, 1-2 parts of catalysts and 1-4 parts of foam stabilizers; the foaming agent comprises sodium dodecyl sulfate, sodium salt of octadecyl alcohol polyoxyethylene ether sulfate, sodium salt of phosphate monoester and phosphogypsum; the foam stabilizer is cellulose starch; the cellulose starch is prepared by reacting carboxymethyl cellulose with epoxy starch; the alkali component comprises water glass and sodium hydroxide; the catalyst is manganese dioxide.
2. A production process for the phosphogypsum autoclaved aerated concrete block as claimed in claim 1, characterized in that: The following steps are involved: (1) ball-milling slag, graphite tailings and quicklime to 190-220 meshes respectively, and mixing them according to the mass ratio to obtain mixed powder; (2) mixing sodium lauryl sulfate, sodium salt of octadecyl alcohol polyoxyethylene ether sulfate, sodium salt of phosphate monoester and phosphogypsum in a mass ratio of 5-7:2:2:1-3, and stirring to obtain a foaming agent; (3) mixing epoxy starch and anhydrous ethanol in a mass ratio of 1:8-10, stirring evenly, adjusting the pH to 3.8-4.2 with glacial acetic acid, adding carboxymethyl cellulose of the same mass as the epoxy starch, stirring at 400-800 rpm for 24 hours, centrifuging and washing with anhydrous ethanol for 3-5 times, and vacuum drying to obtain a foam stabilizer; (4) Mix sodium hydroxide and deionized water, let stand and cool, then add water glass with a modulus of 1.5 to 1.8, stir evenly, let stand for 18 to 24 hours, and prepare an alkali component; (5) Mixing the mixed powder, alkali component, foaming agent, catalyst and foam stabilizer, stirring evenly to obtain slurry, injection molding, pre-curing, autoclaving and curing to obtain phosphogypsum autoclaved aerated concrete blocks.
3. The production process of a phosphogypsum autoclaved aerated concrete block according to claim 2, characterized in that: In the above step (2), the preparation method of octadecanol polyoxyethylene ether sodium sulfate is: heating the octadecanol polyoxyethylene ether to 48-52° C., adding chlorosulfonic acid in an amount of 1 to 1.2 times the mass of the octadecanol polyoxyethylene ether at a rate of 1 to 3 mL / min, reacting for 15 to 25 minutes, heating to 62 to 64° C., adjusting the pH to 8.8 to 9.2 with sodium hydroxide, rotary evaporating and then dissolving with anhydrous ethanol to obtain octadecanol polyoxyethylene ether sodium sulfate.
4. The production process of a phosphogypsum autoclaved aerated concrete block according to claim 2, characterized in that: In the above step (2), the preparation method of the sodium salt of phosphate monoester is as follows: cyclohexane and N,N-dihydroxyethyl dodecylamine are mixed in a mass ratio of 20 to 40:1, and after stirring to dissolve, phosphoric acid in an amount of 4 to 6 times the mass of N,N-dihydroxyethyl dodecylamine is added, the temperature is raised to 85 to 95°C, and the reaction is carried out by keeping the temperature for 3 to 4 hours, and then the temperature is further raised to 110 to 120°C, and the reaction is carried out for 6 to 8 hours, and then sodium hydroxide in an amount of 1.6 to 1.8 times the mass of N,N-dihydroxyethyl dodecylamine is added, and the reaction is carried out for 1 to 2 hours to obtain the sodium salt of phosphate monoester.
5. The production process of a phosphogypsum autoclaved aerated concrete block according to claim 2, characterized in that: In the above step (3), the preparation method of epoxy starch is: starch, ethyl acetate, epichlorohydrin and pyridine are mixed in a mass ratio of 1:6-8:10-20:3, the oil bath is heated to 160-180°C, and the reaction is carried out at 400-600rpm for 2-3h, and the epoxy starch is obtained by suction filtration and washing with anhydrous ethanol for 3-5 times, ultrasonication is carried out at 60-80kHz for 30-60s, and finally drying is carried out.
6. The production process of a phosphogypsum autoclaved aerated concrete block according to claim 2, characterized in that: In the above step (5), the pre-curing temperature is 48-50°C and the time is 4-5 hours; the pressure of the autoclave curing is 0.9-1.1 MPa, the temperature is 160-180°C and the time is 5-6 hours.
Citation Information
Patent Citations
Method for preparing high-performance autoclaved aerated concrete blocks through graphite tailings
CN106365672A
Phosphogypsum foamed thermal building block and preparing method thereof
CN109608149A
Aerated concrete block and preparation process thereof
CN110734300A